Тәлим-тәрбия процесин шөлкемлестириўде оқыўшылардың темпераментлерин есапқа алыў мәселелери - Палўанова, Г.Ж.; Марасулова, Д. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study and description of the physiological and psychological traits of children with different temper- ament (choleric, sanguine, phlegmatic, melancholic) in the educational process.
Keywords: temperament; choleric; sanguine person; phlegmatic person; melancholic; physiology; emotional; dynamics; extremal